Virus kinetics and biochemical derangements among children with Ebolavirus disease. (November 2022) - Kjaldgaard, Lindsey; Claude, Kasereka Masumbuko; Mukadi-Bamuleka, Daniel; Kitenge-Omasumbu, Richard; Dixit, Devika; Edidi-Atani, François; Kuamfumu, Meris Matondo; Bulabula-Penge, Junior; Mambu-Mbika, Fabrice; Tshiani-Mbaya, Olivier; Diaz, Janet; Mulangu, Sabue; et al.
Summary: Background: A paucity of data is available on virologic and biochemical characteristics of paediatric Ebolavirus disease (EVD), compared to adults. Methods: We conducted a retrospective chart review of children (<16 years old) and a comparator group of young adults (16–44 years) from two treatment centres during the 2018–2020 EVD epidemic in Eastern Democratic Republic of the Congo. Statistical methods included chi-squared and Fisher's exact tests (dichotomous and categorical variables), Mann-Whitney U-test (continuous variables), multivariable linear regression (for determinants of admission viral load), linear mixed-effects models (for analysis of longitudinal viral load), and Cox proportional hazard models (to examine risk factors for mortality). Findings: We included 73 children and 234 adults admitted from April to October 2019. Paediatric patients commonly had electrolytes imbalances: hypokalaemia in 26/73 (36%), hyperkalaemia in 38/73 (52%), and hyponatraemia in 54/73 (74%). Hypoglycaemia occurred in 20/73 (27%), acute kidney injury in 43/73 (59%), and rhabdomyolysis in 35/73 (48%). Biochemical abnormalities were detected in a similar proportion of children and adults. The viral load (VL, log10 copies/mL) at admission (7.2 versus 6.5, p =0.0001), the peak viral load (7.5 versus 6.7, p =<0.0001), and the time for viraemia clearance (16 days versus 12 days, p =<0.0001) were significantly different in children. The duration of hospital stay was prolonged in children (20 versus 16 days, p =<0.0001). Risk factors for mortality in children were: VL >7.6 log10 copies/mL, alanine transaminase >525 U/L, C-reactive protein >100 mg/L, blood urea nitrogen >7.5 mmol/L, rhabdomyolysis, and.acute kidney injury. Interpretation: Paediatric EVD patients, like adults, experience multiorgan dysfunction with life-threatening electrolyte imbalances, hypoglycaemia, kidney injury, liver injury, and rhabdomyolysis. Paediatric patients have significantly higher VLs throughout the course of EVD than adults. Funding: This study was not funded.